Tractado de geographia universal, physica, historica, e politica. - Balbi, Adriano (J.P. Aillaud, 1838)
Redigido segundo hum novo plano e conforme aos ultimos tractados de paz, precidido dos principios geraes de geographia astronomica, physica e politica,
with words 未利呢 on title page
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; 22.stamp; Condition: Poor; Géographie historique; Géographie physique; Hard Cover; Histoire universelle; Historical geography; History; Physical geography; Politique mondiale; World history; World politics; physical geography

Tractado de geographia universal, physica, historica, e politica. - Balbi, Adriano (J.P. Aillaud, 1838)
Redigido segundo hum novo plano e conforme aos ultimos tractados de paz; coligido principalmente do tractado de geographia por Adr. Balbi, com addicionamentos tirados dos melhores geographos, particularmente de Malte-Brun e Brué.
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.stamp; Condition: Poor; Géographie historique; Géographie physique; Hard Cover; Histoire universelle; Historical geography; History; Physical geography; Politique mondiale; World history; World politics; physical geography